ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN: STUDI PADA PREMIUM MEMBER UNDIP CAREER CENTER - Anggraeni, Lolita Desy; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2017)
As part part of the changing status of Diponegoro University (Undip) into a Legal Entity State Universities (PTN BH), Undip Career Center (UCC), as an Undip’s career preparation institution, needs to be able to self-finance its operating costs in order to thrive. Instability of Premium Member UCC’s sales rate which ought to be the main source of UCC’s income became the main issue in this study. This study aimed to analyze the factors that might affect the purchasing decision on Premium Member UCC. This research used five variables, namely sales promotion, social media advertising, brand image, product attributes, and purchasing decisions. Sampling of this research was done by using a non-probability sampling with purposive sampling method, in which respondents must be Undip’s 4th semester students and Undip’s fresh graduates. The answers of 110 respondents were then analyzed using Statistical Package for Social Science (SPSS) 23 with Multiple Regressional Analysis as analytical tool. Result showed that sales promotion and social media advertising have a significant positive effect on brand image, and brand image have a significant positive effect on purchasing decisions. Product attributes also has a significant positive effect on purchasing decisions.